Feminism and the Cold War in the U.S. Occupation of Japan, 1945 – 1952 - Mire Koikari (Japan Focus)
On August 15, 1945, World War II came to an end with Japan's unconditional surrender. General Douglas MacArthur, Supreme Commander for the Allied Powers (SCAP), flew from the Philippines to Japan with a mission to occupy and demilitarize the defeated nation. The place and manner of MacArthur’s arrival seemed to signal the victor’s absolute confidence and unquestioned authority over its vanquished enemy. MacArthur – the embodiment of U.S. military power and a consummate actor well known for his grand performance – landed at the Atsugi Airfield, previously a training field for Japanese kamikaze fighters, with a handful of Allied troops. MacArthur himself was armed only with a corncob pipe. Despite his staff’s concern about possible attacks by enemy soldiers not yet disarmed, MacArthur’s triumphant landing was followed by a smooth procession to the New Grand Hotel in Yokohama and later an entry into Tokyo where he established the General Headquarters (GHQ) of SCAP in the Dai-ichi Seimei Insurance Building. A new chapter of postwar U.S.-Japan relations thus opened with richly gendered and racialized symbolism: the United State’s imposition of white masculine military authority over Japan, now a defeated and subjugated nation in the Far East.